Implementing the Merdeka Curriculum in Remote Primary Schools: School Leadership and Adaptive Strategies in Indonesia's 3T Regions - Sahbana Ridha; Ahmad Suriansyah; Sulistiyana (The Indonesian Institute of Science and Technology Research, 2026)
This study examines school management challenges in implementing Indonesia's Merdeka Curriculum across three primary schools in remote, frontier, and disadvantaged (3T) regions of South Kalimantan Province. Although the curriculum is designed to promote flexibility and contextual learning, its implementation in marginalized settings encounters constraints related to human resources, infrastructure, supervision, leadership capacity, and the need for local policy adaptation. Using a qualitative multiple case study design, data were collected through in-depth interviews with principals and teachers, participant observation, and document analysis at three schools representing distinct geographic conditions: a mountainous site, a swampland site, and a riverine site. Data were analyzed thematically using an interactive model, with cross-case comparison employed to identify convergent and divergent patterns. Findings indicate that principals adopt adaptive and collaborative leadership strategies including contextualizing curriculum to local livelihoods, mobilizing community resources, and providing internal coachingto sustain implementation despite resource limitations. However, the schools differ in the degree of external support and supervision they receive, revealing that implementation outcomes are shaped less by curriculum design alone than by the responsiveness of multi-level support systems. The study contributes empirically by documenting authentic implementation experiences in under-researched 3T contexts and offers practical implications for strengthening teacher capacity, infrastructure equity, and context-responsive leadership development. Rather than indicating local failure, the documented challenges underscore the need for sustained, coordinated investment in marginalized education.